2003
DOI: 10.1089/153968503321642642
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models for the Study of Lymphatic Insufficiency

Abstract: Lymphedema is the term commonly employed to describe the spectrum of pathological states that arise as a consequence of functional lymphatic insufficiency. These human disease entities currently lack an effective cure. Satisfactory therapeutic strategies for both primary and secondary lymphedema will require additional insight into the complex cellular mechanisms and responses that comprise both normal lymphatic function and its regional derangement in states of pathologic dysfunction. Such insights must, init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 44 publications
0
51
0
3
Order By: Relevance
“…Surprisingly, all dogs showed improvement of their lymphedema irrespective of the group, suggesting that lympho-lymphatic anastomosis in microsurgical lymph node transplantation has little clinical relevance. Regrettably, no dog presented a complete resolution of the disease (6).…”
Section: Beginnings With Canine Modelsmentioning
confidence: 97%
See 3 more Smart Citations
“…Surprisingly, all dogs showed improvement of their lymphedema irrespective of the group, suggesting that lympho-lymphatic anastomosis in microsurgical lymph node transplantation has little clinical relevance. Regrettably, no dog presented a complete resolution of the disease (6).…”
Section: Beginnings With Canine Modelsmentioning
confidence: 97%
“…This model was used to study lymphaticovenous microanastomoses (as reviewed in ref. 6). Researchers showed that postoperative pressure gradients between the lymph and venous blood were inversed when lymphedema tended to resolve, thus causing lymph reflux and thrombosis of the anastomosis.…”
Section: Beginnings With Canine Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was considered to be indicative of insufficient drainage of the lymph that had flowed from the extracellular fluid into the lymph vessels. 8,9) Normal lymph vessels are straight in form, but in cases of lymphostasis, their lumens become enlarged, as is seen in , and 28 days after the procedure, the lymphatic vessels in the lymphatic insufficiency model tissue exhibited significantly greater diameters than those in the control tissue (*P <0 .05). (C) At 28 days after the procedure, the number of lymphatic vessels in the lymphatic insufficiency model tissue was lower than that seen in the control tissue (n = 5, *P <0.05).…”
Section: Presence Of Lymphatic Insufficiency In the Animal Modelmentioning
confidence: 88%